2013
DOI: 10.1111/tran.12040
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of neighbourhood poverty: an analysis of neighbourhood histories of individuals

Abstract: The extent to which socioeconomic (dis)advantage is transmitted between generations is receiving increasing attention from academics and policymakers. However, few studies have investigated whether there is a spatial dimension to this intergenerational transmission of (dis)advantage. Drawing on the concept of neighbourhood biographies, this study contends that there are links between the places individuals live with their parents and their subsequent neighbourhood experiences as independent adults. Using indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 49 publications
7
132
0
8
Order By: Relevance
“…To the contrary, particularly the ethnic composition of the neighborhood was found to be more stable over time among children from immigrant families than among native Dutch children. These findings are in line with previous research (Quillian 2003;van Ham et al 2014) suggesting that ethnic minority children have a stronger persistence of neighborhood disadvantage than children from the majority population.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To the contrary, particularly the ethnic composition of the neighborhood was found to be more stable over time among children from immigrant families than among native Dutch children. These findings are in line with previous research (Quillian 2003;van Ham et al 2014) suggesting that ethnic minority children have a stronger persistence of neighborhood disadvantage than children from the majority population.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, in other words, especially those young people who have been consistently exposed to socioeconomically deprived neighborhoods may experience negative outcomes. Despite the fact that research increasingly recognizes the importance of the temporal dynamics of childhood disadvantage, children's neighborhood characteristics are still frequently measured at a single point in time (e.g., Assari et al 2016;de Vuijst, van Ham, and Kleinhans 2015;Page and Solon 2002;van Ham et al 2014). Whether or not such point-in-time measures serve as valid proxies for the neighborhood conditions that children endure in the long run depends on the amount of continuity or change in children's neighborhood environment over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of neighbourhood effects investigate the instantaneous effects of single pointin-time measurements of neighbourhood environments on individual outcomes. However, it has repeatedly been suggested that most theories of neighbourhood effects assume medium to long-term exposure to poverty neighbourhoods for there to be an effect Musterd et al, 2012;van Ham et al, 2012c).…”
Section: Ten Challenges For Neighbourhood Effects Researchmentioning
confidence: 99%
“…The poor environment and neighbourhood theme posited that parents' characteristics and parenting styles are significantly influenced by the neighbourhood and environment (Pinderhughes et al, 2001;Caughy et al, 2003;Leventhal and BrooksGunn, 2003;Barnes, 2004;Gutman et al, 2005;Van Ham et al, 2014).…”
Section: Poor Environments and Neighbourhoodsmentioning
confidence: 99%